Influence of Process Parameters on the Morphology of Spray‐Dried BaCl2 Powders. Issue 1 (24th September 2015) - Shoulders, W. Taylor; Bizarri, Gregory; Bourret, Edith; Gaume, Romain M.
Abstract : Spray‐drying is an effective method for producing powder aggregates with controlled size and morphology. Here, we report on a systematic study aimed at determining how spray‐drying parameters such as nozzle temperature, gas flow, salt concentration and solution feed rate, influence the characteristics of BaCl2 granules prepared from aqueous solutions. We correlate the granule characteristics to these conditions through the use of processing maps and modeling. It is found that well‐dispersed, high density and spherical aggregates, which are favorable for subsequent powder compaction and sintering, can be obtained within a limited range of processing conditions.